(untitled) (LEARNing Landscapes, 2009)
In this interview, three grade six students discuss their perspectives on literacy. Sonora, Shannon, and Benoît explore the role of peer collaboration, fun, and the various ways that they learn and share their learning with others. The students express their enjoyment of reading and emphasize the value of challenging oneself and persevering when a book or a project becomes difficult.They explain the advantages of pneumonic devices and other "tricks" for learning items such as multiplication tables, and elaborate with anecdotes involving fellow students as well as adults. Common to all of the students’ experiences are the benefits of multi-modal teaching and learning, and the advantages of incorporating art with auditory and visual information in literacy activities. These students also discuss the Internet as an important resource, citing its use for classroom inquiry as well as educational games. They recognize the importance of literacy for future success. Their advice to others is to work hard in school.